Proteção jurídica do bioma caatinga - Lima, João Paulo Alves de (2016)
The New Forest Code, Law 12,651/2012, severely reflected in the unique biome: Caatinga. In full affront to the constitutional principle of non-retrogression of environmental protection, the new standard acts as a catalyst agent of desertification and extinction of this biome exclusively Brazilian. The Caatinga, to Brazil has historical, social, cultural and economic importance that impacts on biological, geological, climatic aspects and can bring social consequences of irreparable and irreversible damage not only to the environment but also to future generations that depend on it for their livelihood. This research reflects the continuity of the biome as a peculiarity and uniqueness of Brazil. It is important to open national and international projects to enable the change of the energetic matrix and the exclusion of legal threats imposed to the biome.